Patient-public engagement strategies for health system improvement in sub-Saharan Africa: a systematic scoping review - Samuel Egyakwa Ankomah; Adam Fusheini; Christy Ballard; Emmanuel Kumah; Gagan Gurung; Sarah Derrett (BMC, 2021)
Abstract Background Actively involving patients and communities in health decisions can improve both peoples' health and the health system. One key strategy is Patient-Public Engagement (PPE). This scoping review aims to identify and describe PPE research in Sub-Saharan Africa; systematically map research to theories of PPE; and identify knowledge gaps to inform future research and PPE development. Methods The review followed guidelines for conducting and reporting scoping reviews. A systematic search of peer-reviewed English language literature published between January 1999 and December 2019 was conducted on Scopus, Medline (Ovid), CINAHL and Embase databases. Independent full text screening by three reviewers followed title and abstract screening. Using a thematic framework synthesis, eligible studies were mapped onto an engagement continuum and health system level matrix to assess the current focus of PPE in Sub-Saharan Africa. Results Initially 1948 articles were identified, but 18 from 10 Sub-Saharan African countries were eligible for the final synthesis. Five PPE strategies implemented were: 1) traditional leadership support, 2) community advisory boards, 3) community education and sensitisation, 4) community health volunteers/workers, and 5) embedding PPE within existing community structures. PPE initiatives were located at either the 'involvement' or 'consultation' stages of the engagement continuum, rather than higher-level engagement. Most PPE studies were at the 'service design' level of the health system or were focused on engagement in health research. No identified studies reported investigating PPE at the 'individual treatment' or 'macro policy/strategic' level. Conclusion This review has successfully identified and evaluated key PPE strategies and their focus on improving health systems in Sub-Saharan Africa. PPE in Sub-Saharan Africa was characterised by tokenism rather than participation. PPE implementation activities are currently concentrated at the 'service design' or health research levels. Investigation of PPE at all the health system levels is required, including prioritising patient/community preferences for health system improvement.